Model and data engineering : 7th International Conference, MEDI 2017, Barcelona, Spain, October 4-6, 2017, Proceedings /: 7th International Conference, MEDI 2017, Barcelona, Spain, October 4-6, 2017, Proceedings. (2017) - Unknown
No abstract available